Penal Code, ch. 43, §§ 549-550, MONTGOMERY, CODE OF ORDINANCES 213, 223-29 (1888 Brown Printing Co.) (Montgomery, Alabama). - (:unkn) unknown (General Publisher, 1888)
Any person who carries or causes to be carried, any powder upon any vehicle, without having the same so arranged as effectually to cover up the packages or kegs, and guard them from public view and from accident from fire, must, on conviction, be fined not less than one nor more than one hundred dollars.Any person who receives or delivers any powder or matches concealed in any manner and purporting to be any other article or commodity, must, on conviction, be fined not less than one nor more than one hundred dollars.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER